Antioxidant and Cardioprotective Effects of EPA on Early Low-Severity Sepsis through UCP3 and SIRT3 Upholding of the Mitochondrial Redox Potential. (26th August 2019) - Leger, Thibault; Azarnoush, Kasra; Traoré, Amidou; Cassagnes, Lucie; Rigaudière, Jean-Paul; Jouve, Chrystèle; Pagès, Guilhem; Bouvier, Damien; Sapin, Vincent; Pereira, Bruno; Bonny, Jean-Marie; Demaison, Luc
Abstract : Sepsis still causes death, often through cardiac failure and mitochondrial dysfunction. Dietary ω 3 polyunsaturated fatty acids are known to protect against cardiac dysfunction and sepsis lethality. This study set out to determine whether early low-severity sepsis alters the cardiac mitochondrial function in animals fed a Western-type diet and whether dietary eicosapentaenoic acid (EPA) administration protects the myocardium against the deleterious effects of sepsis and if so to seek possible mechanisms for its effects. Rats were divided into two groups fed either an ω 3 PUFA-deficient diet ("Western diet, " DEF group) or an EPA-enriched diet (EPA group) for 5 weeks. Each group was subdivided into two subgroups: sham-operated rats and rats subjected to cecal ligation and puncture (CLP). In vivo cardiac mechanical function was examined, and mitochondria were harvested to determine their functional activity. Oxidative stress was evaluated together with several factors involved in the regulation of reactive oxygen species metabolism. Sepsis had little effect on cardiac mechanical function but strongly depressed mitochondrial function in the DEF group. Conversely, dietary EPA greatly protected the mitochondria through a decreased oxidative stress of the mitochondrial matrix. The latter was probably due to an increased uncoupling protein-3 expression, already seen in the sham-operated animals. CLP rats in the EPA group also displayed increased mitochondrial sirtuin-3 protein expression that could reinforce the upholding of oxidative phosphorylation. Dietary EPA preconditioned the heart against septic damage through several modifications that protect mitochondrial integrity. This preconditioning can explain the cardioprotective effect of dietary EPA during sepsis.